2016
DOI: 10.1063/1.4955411
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic spectral characteristics measurement of DFB interband cascade laser under injection current tuning

Abstract: The dynamic spectral properties of semiconductor lasers during its tuning are very important for frequency modulation-based applications. The spectral properties of a distributed feedback (DFB) interband cascade laser (ICL) under injection current tuning (i.e., slope efficiency, dynamic tuning rate, and instantaneous linewidth) were measured by using short delayed self-heterodyne interferometry combined with time-frequency analysis of the interferometric signal. The relations of these spectral characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…This value is higher than for a QCL, but generally lower than for interband lasers emitting at shorter wavelengths. While an earlier frequency-modulation study of DFB ICLs [232] found a much larger intrinsic linewidth (> 300 kHz), that measurement may have been influenced by noise from the driver current [233].…”
Section: Linewidth and Stabilitymentioning
confidence: 71%
See 1 more Smart Citation
“…This value is higher than for a QCL, but generally lower than for interband lasers emitting at shorter wavelengths. While an earlier frequency-modulation study of DFB ICLs [232] found a much larger intrinsic linewidth (> 300 kHz), that measurement may have been influenced by noise from the driver current [233].…”
Section: Linewidth and Stabilitymentioning
confidence: 71%
“…Because the noise decreases with increasing frequency, techniques such as wavelength modulation spectroscopy (WMS) and frequency modulation spectroscopy (FMS) can provide much more sensitive chemical detection [232]. When a small sinusoidal modulation is added to the slow current sweep of a tunable laser, the magnitude and shape of the multiple harmonic orders that are produced can provide information about the concentration and temperature of the absorbing species.…”
Section: Linewidth and Stabilitymentioning
confidence: 99%
“…DFB-ICLs provide single mode, narrow linewidth (~0.7 MHz) [62], low power consumption (hundreds of milliwatts), a compact system solution, and RT-cw emission in the 3-6 µm range, which fill the MIR gap perfectly. DFB-ICLs have been used for the ppb-level detection of many important gases, especially hydrocarbon species [63][64][65][66][67][68][69], which leads to many important applications in various areas, for example, clinical diagnostics [70,71], combustion probing [72], environmental monitoring [73,74], and remote sensing.…”
Section: Interband Cascade Lasersmentioning
confidence: 99%
“…We carefully set all the working parameters of the sensor, including the optical path, gas flow, modulation amplitude, temperature, and so on. The instantaneous line width, dynamic tuning rate, and slope efficiency of ICLs have been reported to be suitable for precision spectroscopy measurements [ 36 ]. The laser power before and after HWG were 5.5 mW and 0.9 mW, respectively.…”
Section: Sensor Configurationmentioning
confidence: 99%